Influence of spent shea waste addition on the technological properties of fired clay bricks. (May 2017) - Adazabra, A.N.; Viruthagiri, G.; Kannan, P.
Abstract: This paper examines the feasibility of replacing clay materials with spent shea waste as an economic and sustainable construction material via assessing the technological properties of their fired brick bars. In this regard, we admix different proportions of spent shea waste to the raw clay materials. Rectangular brick bars were prepared through the replacement of 5, 10, 15 and 20 wt% of the clay materials with spent shea waste. Preliminarily, the waste and clay materials were characterized by their chemical composition, X-ray powder diffraction, particle morphologies and thermal behaviour. The prepared brick bars were sintered at temperatures ranging from 900 °C to 1200 °C and their technological properties (e.g. linear dry shrinkage, green density, linear fired shrinkage, fired density, apparent porosity, compressive strength and water absorption) were ascertained. It was found that spent shea waste is an excellent calorific value material, which contained minor concentrations of SiO2 (0.35 wt%), Al2 O3 (0.37 wt%), K2 O (2.11 wt%), CaO (2.11 wt%) and a rich diversity of inorganic fluxes in trace amounts. The test results show that spent shea waste could synergistically be used as energy-contributing raw materials in construction brick; thus, creating new pathways of possibilities for their widespread economic and sustainable reuse in the construction industry. Graphical abstract: Highlights: Reusing spent shea waste in fired brick production instead of landfilling them. Optimized production conditions for spent shea waste bricks were determined. Reusing spent shea waste in brick construction was beneficial and promising. Statistical analysis of the consistency levels of molding additive clay bricks.